The Roles of Jakarta Old Town Area Managers in Creating First Impressions of Tourists - Desy Nur Aini Fajri; Nadia Asti Nurmayningsih (Departemen Pariwisata Universitas Negeri Padang, 2026)
This study aims to analyze the role of area managers in creating first impressions of tourists in Jakarta Tua City, focusing on three main aspects, namely the physical environment (servicescape), service quality (SERVQUAL), and information provision. As one of the cultural heritage areas with high historical value, Jakarta Old Town is a leading destination that attracts domestic and foreign tourists. This study uses a qualitative approach. Data collection techniques are carried out through in-depth interviews, observations, documentation, and literature studies. Meanwhile, the data analysis technique is carried out in three stages, namely data reduction, data presentation, and conclusion drawn. The results of the study show that the area managers have made various efforts in building a positive first impression for tourists. These efforts include physical revitalization of the area, improving the quality of public services, and developing information systems, both online and offline, which are designed to provide a positive experience towards tourists.